A novel triphenylamine functionalized bithiazole–metal complex with C60 for photocatalytic hydrogen production under visible light irradiation1. Issue 12 (28th March 2015) - Huo, Jingpei; Zeng, Heping
<x xml:space="preserve">Abstract</x> Composite 6 (2.0 wt% C60) is an efficient and fully recyclable catalyst for photocatalytic H2 production (7.39 mmol h−1 g−1) under visible light illumination.